Peer Support Increases Maternal Confidence, Kangaroo Mother Care Implementation and Weight Gain in LBW Infants. (29th March 2019) - Kurniawati,; Rustina, Yeni; Budiati, Tri
ABSTRACT: Weight gain in low birth weight infants can be improved by Kangaroo Mother Care (KMC). The sustainability of KMC implementation can be improved by increasing maternal confidence. Therefore, an appropriate method is needed in KMC education so that maternal confidence, KMC implementation, and weight gain in low birth weight infants can be increased. This study aimed to determine the effect of peer support on maternal self-confidence, KMC implementation, and infant's weight gain in four hospitals: one hospital in Jakarta, Bogor, Tangerang, and Bekasi. The study design was a randomized controlled trial with pre-post test equivalent group which involved 24 participants in both intervention and control group, respectively, based on selected criteria. The intervention provided was three sessions of education on KMC based on individual approach provided by peers. The KMC implementation and infant's weight gain were observed for five days. This study employed a maternal self-confidence questionnaire and KMC observation and weight gain form. The result showed significant differences in mother's confidence, KMC implementation, and infant's weight gain between the control group and intervention group ( p = 0.001; 0.001; 0.032; 0.030). There was a significant correlation between infant's birth weight, maternal self-confidence and infant's weight gain, as well as between comorbidities and weight gain in infants. So, peer support effectively improved maternal self-confidence, KMC implementation, and weight gain in infants in hospital. Therefore, the implementation may be extended throughout home visits.